Klotho inhibits PKCα/p66SHC-mediated podocyte injury in diabetic nephropathy. (20th August 2019) - Jiang, Wei; Xiao, Tangli; Han, Wenhao; Xiong, Jiachuan; He, Ting; Liu, Yong; Huang, Yinghui; Yang, Ke; Bi, Xianjin; Xu, Xinli; Yu, Yanlin; Li, Yan; et al.
Abstract: Diabetic nephropathy (DN) is a progressive disease, the main pathogeny of which is podocyte injury. As a calcium-dependent serine/threonine protein kinase involved in podocyte injury, protein kinase C isoform α (PKCα) was reported to regulate the phosphorylation of p66SHC. However, the role of PKCα/p66SHC in DN remains unknown. Klotho, an anti-aging protein with critical roles in protecting kidney, is expressed predominantly in the kidney and secreted in the blood. Nonetheless, the mechanism underlying amelioration of podocyte injury by Klotho in DN remains unclear. Our data showed that Klotho was decreased in STZ-treated mice and was further declined in diabetic KL ± mice. As expected, Klotho deficiency aggravated diabetes-induced proteinuria and podocyte injury, accompanied by the activation of PKCα and p66SHC. In contrast, overexpression of Klotho partially ameliorated PKCα/p66SHC-mediated podocyte injury and proteinuria. In addition, in vitro experiments showed that activation of PKCα and subsequently increased intracellular reactive oxygen species (ROS) was involved in podocytic apoptosis induced by high glucose (HG), which could be partially reversed by Klotho. Hence, we conclude that Klotho might inhibit PKCα/p66SHC-mediated podocyte injury in diabetic nephropathy. Graphical abstract: Schematic diagram of the proposed mechanism. HG promotes calcium influx by activating calcium channel (e.g. TRCPC6) in podocytes. Excess intracellular calcium activates PKCα which then contributes to the phosphorylation of p66SHC. Phosphorylated p66SHC then enters mitochondria by altering its configuration. Thereafter, the altered configuration of p66SHC oxidizes cytochrome c (Cytc) releasing a large amount of reactive oxygen species (ROS). Continuous generation of ROS eventually leads to cellular injury and apoptosis of podocytes. However, Klotho (sKL) can function by inhibiting calcium influx induced by HG. SKL reduces intracellular calcium to inhibit PKCα/p66SHC. Therefore, Klotho inhibits continuous generation of ROS eventually ameliorating injury and apoptosis of podocytes.Image 1 Highlights: Klotho was inhibited in STZ-treated mice and was further declined in diabetic KL ±mice. Klotho deficiency aggravated diabetic-induced proteinuria and podocyte injury. Klotho deficiency aggravated the activation of PKCα and p66SHC. Klotho reversed activation of PKCα/p66SHC and ROS generation induced by HG in vitro. Overexpression of Klotho ameliorated PKCα/p66SHC-mediated podocyte injury.